Evaluasi Program Pembelajaran Tilawah Qur’an Dengan Menggunakan Model CIPP Di MTs Swasta Cendekia Medan - Elysa, Elysa (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research aims to review the process and implementation of evaluating Al-Qur'an Recitations using the CIPP model. Through the Al-Qur'an recitation program, students can gain insight into knowledge of how to read, recite and write verses of the Al-Qur'an by knowing the rules that have been set, such as mahkorijul letters, short lengths, tajwid rules, and ghorib so that they do not there is a change in meaning. This research problem focuses on the evaluation of the CIPP System for the Al-Qur'an Recitation Program at Private MTs Cendikia. This research aims to find out: 1) the implementation of Al-Qur'an recitation program activities at the Private Scholar MTs. 2) evaluate the Al-Qur'an recitation program using the CIPP system at MTS Private Scholar. The type of research that will be carried out in this research is qualitative field research. The subject of this research is: Tahfiz teacher in applying recitations of the Qur'an at the Private Scholar MTs. The data collection techniques required are observation and documentation. As well as data analysis using data reduction, data display, and conclusion drawing/verification.